Insights and Questions Arising from Studies of a Mouse Model of Glanzmann Thrombasthenia - Hynes, Richard O.; Hodivala-Dilke, Kairbaan M. (Thrombosis and Haemostasis, 1999)
Studies of patients suffering from Glanzmann thrombasthenia (GT) have provided many insights into the role of platelet adhesion in hemostasis and thrombosis,1-3 but they also have raised some unanswered questions. This genetically inherited bleeding disorder arises from mutations in the genes for either subunit of the major platelet integrin, αIIbβ3, or glycoprotein IIb/IIIa (CD41/CD61). These mutations lead to reduced or absent expression of this integrin on platelet surfaces or, in a few cases, to normal levels of expression of functionally defective forms of αIIbβ3.1-6 Normally, αIIbβ3 functions as one of the major adhesion receptors on platelets. It also serves as a receptor for fibrinogen during platelet aggregation and as a receptor for von Willebrand factor (vWF) during platelet adhesion to a damaged vessel wall.7,8 In addition, αIIbβ3 can also act as a fibronectin receptor9,10 or a thrombospondin receptor,11 though the exact importance of these interactions in platelet adhesion and/or aggregation remains unclear.GT patients lacking αIIbβ3, or who express reduced levels or defective forms, have a number of characteristic defects in platelet function. These include defective platelet aggregation in response to a variety of agonists, failure to retract a fibrin clot, and reduced or absent intracellular fibrinogen.1-4 Patients show prolonged bleeding times and spontaneous mucocutaneous and gastrointestinal hemorrhage. Occasional bleeding crises can usually be managed by platelet transfusions, so the mortality is relatively low. Both male and female patients are fertile, and pregnancies can be carried to term, although postpartum hemorrhage and menorrhagia can occur.The features of GT described above are common among patients with mutations in the αIIβ gene or the β3 gene. At one level, that is to be expected, since absence of either subunit destroys the functional heterodimeric integrin, and, indeed, compromises the export of the partner subunit to the surface. As a result, the partner subunit is degraded intracellularly.1-4 However, a complication arises in that the β3 subunit can also partner with another subunit, αv. The αvβ3 receptor is normally present at low levels (50 to 100 copies per platelet compared with 40,000 to 80,000 copies of αIIbβ3 per platelet), and its levels reportedly do not change on GT platelets lacking αIIb. Naturally, it is absent from β3-null platelets, but no defects attributable to the additional absence of αvβ3 have been described.Given the low levels of αvβ3 on platelets, one might not expect a serious hemostatic consequence associated with its loss. However, αvβ3 is also expressed by many other cell types, in contrast with αIIbβ3, which is platelet-specific. Most notably, αvβ3 is expressed by endothelial cells during angiogenesis and has been implicated functionally in angiogenesis.12,13 It is also apparently an integrin of major importance on osteoclasts, where it is believed to play a role in bone remodeling.14,15 The αvβ3 receptor is also expressed by neutrophils, monocytes, macrophages, some T cells, melanomas, glioblastomas, and neural crest cells, among others.16-20 Given this widespread expression and the data implicating αvβ3 in important developmental and physiological processes, one would have predicted that mutations in the β3 gene would have much more severe consequences than the platelet-specific defects associated with mutations in the αIIb gene. Nonetheless, the clinical data on GT patients have failed to reveal clear distinctions between those defective in αIIb and those defective in β3.1-4 At least some of the β3 mutations are nulls, so it is unclear whether such GT patients might exhibit additional defects, for example in angiogenesis, wound repair, or bone remodeling. A few studies have been performed involving limited numbers of GT patients, but there are obvious limitations to the extent of experimentation that can be performed on these patients. Simply put, there are few GT patients, and ethical considerations severely limit possible interventions.